Gender, Familial Ideologies, and Aspects of Genre in the Early-Republic Murder Trial Report (Altre Modernità, 2016)
The present essay focuses on a case of matricide which happened in New Jersey in 1812. Mary and Cornelius Cole, a married couple, were charged with the murder of Mary’s mother, Agnes Thuers. While Cornelius denied any involvement in the actual killing, and only admitted to assisting his wife in concealing the crime and disposing of the body, Mary confessed but claimed that she had killed Thuers in self-defence. She was convicted and hanged for this crime whereas her husband was sentenced to two years in prison as an accessory. The case was swiftly turned into two criminal narratives: A Genuine Sketch of the Trial of Mary Cole for the Wilful Murder of her Mother, Agnes Thuers (1812) and The Confession of Mary Cole (1813). The essay demonstrates how the strategies and techniques employed to construct, fictionalize, and present the tormented mother-daughter relationship to the reading public, offer a privileged insight into the dominant familial and gender ideologies of the time.